(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Infertility is a worldwide problem and in almost 50% of cases infertility results from abnormality of the male partners. Apart from endocrine disorders, definitive cause and mechanism of male infertility is not clear in many cases. Recent evidence indicates that imbalance between pro-oxidant stress and antioxidant defense plays an important role in the pathogenesis of male infertility. Among the endogenous antioxidant systems, reduced glutathione (GSH) plays a significant role in the antioxidant defense of the spermatogenic epithelium, the epididymis and perhaps in the ejaculated spermatozoa. The current study was therefore designed to evaluate any association that may exist between GSH levels and male infertility. Infertile male patients (having female partners with normal fertility parameters; n=31) and age- matched healthy male fertile control subjects (n=30) were included in this study. In addition to medical history, semen analyses including semen volume, sperm count, motility and morphology were done for each subject. As a measure of antioxidant capacity erythrocyte and seminal plasma GSH concentrations were measured by Ellman’s method in fertile and infertile male subjects. The infertile subjects were similar to fertile subjects in terms of age. However, semen volume and sperm count was found significantly lower (p<0.001) in infertile males compared with healthy fertile male subjects. Percentage of subjects with abnormal sperm morphology and motility were found higher in infertile group compared with fertile group. The median (range) erythrocyte GSH level did not differ between the two groups (12.62 (0.67-29.82) versus 13.93 (2.10-21.08) mg/gm Hb). However, the seminal plasma GSH level was found markedly suppressed in infertile group (1.64 (0.23-7.50)) compared with fertile group (4.26 (2.32-7.50)) mg/dl (p<0.001). In the present study seminal plasma GSH level was found markedly suppressed along with abnormal values for semen volume, sperm concentration and sperm morphology and motility in infertile subjects compared with fertile subjects. This finding indicates that low level of seminal plasma GSH level may be associated with male infertility. DOI: http://dx.doi.org/10.3329/bjmb.v4i2.13772 Bangladesh J Med Biochem 2011; 4(2): 20-25